THE INFLUENCE OF WORD OF MOUTH AND CUSTOMER MOTIVATIONS ON CONSUMER BUYING BEHAVIOR AT PONDOK TETERUSAN RESTAURANT - David, Ezara Daniella (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Consumer preferences and tastes constantly change. It is important for marketers to know what consumer needs and wants, how they spend their resources, how they decided to shop, visit, to eat, when to buy, and what to purchase. Experiences is one of the major factors of how customer make a decision. Good experiences means good viral marketing. Consumers value word of mouth twice as much as they value advertising. The objectives of this research are to analyze the influence of word of mouth towards customer motivations, the influence of word of mouth towards consumer buying behavior, and the influence of word of mouth and customer motivations towards consumer buying behavior. This research is a quantitative research and uses causal type of research. And the data used in this study is Path Analysis. This research refers to people who live in Manado who ever visit Pondok Teterusan restaurant. The sample of this research is 100 respondents. This study reveals that there is a significant influence between word of mouth and customer motivations on consumer buying behavior, word of mouth has a significant influence towards customer motivations, and word of mouth has a significant influence towards consumer buying behavior. Keywords: consumer buying behavior, motivation, word of mouth